Water-absorbent resin particles, absorbent body and absorbent article

JP7629850B2Active Publication Date: 2025-02-14SUMITOMO SEIKA CHEM CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021516060
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-23
Filing Date
2020-04-16
Publication Date
2025-02-14
Estimated Expiration
2040-04-16

AI Technical Summary

Benefits of technology

【0009】 本発明の一側面によれば、使用時の液体漏れが抑制された吸収性物品を得ることが可能な吸水性樹脂粒子を提供することができる。本発明の他の一側面によれば、当該吸水性樹脂粒子を用いた吸収体及び吸収性物品を提供することができる。本発明の他の一側面によれば、吸液への樹脂粒子、吸収体及び吸収性物品の応用を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629850000002
    Figure 0007629850000002
  • Figure 0007629850000003
    Figure 0007629850000003
  • Figure 0007629850000004
    Figure 0007629850000004
Patent Text Reader

Abstract

Disclosed herein are water-absorbent resin particles having a degradation rate of 15% or less in the value for unpressurized DW after three minutes as measured according to the following procedure. (1) 15 g water-absorbent resin particles are placed in a 1 L-capacity stainless steel mixing vessel. (2) A degradation treatment is performed on the water-absorbent resin particles by rotating the mixing vessel, in which the water-absorbent resin particles have been placed, for two hours at a rotation speed of 45 rpm and a revolution speed of 45 rpm. (3) The degradation rate in the value for unpressurized DW after three minutes as calculated according to the following formula, in which I is the value for the unpressurized DW of the water-absorbent resin particles after three minutes before the degradation treatment and II is the value for the unpressurized DW of the water-absorbent resin particles after three minutes after the degradation treatment, is obtained. Formula: [(I – II) / I] × 100
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to water-absorbent resin particles, an absorbent body, and an absorbent article. [Background technology]

[0002] Conventionally, absorbent articles for absorbing liquids mainly composed of water (e.g., urine) use absorbents containing water-absorbent resin particles. For example, Patent Document 1 below discloses water-absorbent resin particles having a particle size suitable for use in absorbent articles such as diapers. Patent Document 2 also discloses a method of using a hydrogel absorbent polymer having specific saline flow conductivity, pressure performance, etc. as an absorbent member effective for storing body fluids such as urine. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 06-345819 [Patent Document 2] Special Publication No. 09-510889 Summary of the Invention [Problem to be solved by the invention]

[0004] It is desirable to prevent liquid leakage from an absorbent article during use as much as possible.

[0005] An object of one aspect of the present invention is to provide a water-absorbent resin particle capable of obtaining an absorbent article in which liquid leakage during use is suppressed. Another object of the present invention is to provide an absorbent body and an absorbent article using the water-absorbent resin particle. [Means for solving the problem]

[0006] One aspect of the present invention relates to water-absorbent resin particles having a deterioration rate of 15% or less at 3 minutes of no-pressure DW measured by the following procedure. (1) 15 g of water-absorbent resin particles are placed in a 1 L stainless steel mixing vessel. (2) The mixing vessel in which the water-absorbent resin particles are placed is rotated for 2 hours under conditions of a rotation speed of 45 rpm and a revolution speed of 45 rpm, thereby subjecting the water-absorbent resin particles to a deterioration treatment. (3) When a 3-minute value of no pressure DW of the water absorbent resin particle before the deterioration treatment is I and a 3-minute value of no pressure DW of the water absorbent resin particle after the deterioration treatment is II, a deterioration rate at the 3-minute value of no pressure DW is calculated by the following formula. [(I-II) / I] x 100

[0007] According to the above-mentioned water-absorbent resin particles, it is possible to obtain an absorbent article in which liquid leakage during use is suppressed.

[0008] Another aspect of the present invention provides an absorbent body containing the above-mentioned water-absorbent resin particles. Another aspect of the present invention provides an absorbent article including the above-mentioned absorbent body. Effect of the Invention

[0009] According to one aspect of the present invention, it is possible to provide water-absorbent resin particles capable of obtaining an absorbent article in which liquid leakage during use is suppressed. According to another aspect of the present invention, it is possible to provide an absorbent body and an absorbent article using the water-absorbent resin particles. According to another aspect of the present invention, it is possible to provide application of the resin particles, the absorbent body and the absorbent article to liquid absorption. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view showing one embodiment of an absorbent article. [Diagram 2] FIG. 2 is a plan view showing the general shape of the stirring blade used in the examples. [Diagram 3] FIG. 1 is a schematic diagram showing an example of a method for measuring non-pressure DW. [Figure 4] FIG. 2 is a schematic diagram showing an example of a method for measuring a deterioration rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, several embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments.

[0012] In this specification, "acrylic" and "methacrylic" are collectively referred to as "(meth)acrylic". "Acrylate" and "methacrylate" are also collectively referred to as "(meth)acrylate". "(Poly)" refers to both the case with and without the prefix "poly". In the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain numerical range can be arbitrarily combined with the upper limit or lower limit of the numerical range of another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. "A or B" may include either A or B, or may include both. "Water-soluble" means that the material has a solubility of 5% by mass or more in water at 25°C. The materials exemplified in this specification may be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.

[0013] The water-absorbent resin particles according to one embodiment have a deterioration rate of 15% or less at 3 minutes of no-pressure DW measured by the following procedure. (1) 15 g of water-absorbent resin particles are placed in a 1 L stainless steel mixing vessel. (2) The mixing vessel in which the water-absorbent resin particles are placed is rotated for 2 hours under conditions of a rotation speed of 45 rpm and a revolution speed of 45 rpm, thereby subjecting the water-absorbent resin particles to a deterioration treatment. (3) When the 3-minute value of the non-pressurized DW of the water absorbent resin particle before the deterioration treatment is I and the 3-minute value of the non-pressurized DW of the water absorbent resin particle after the deterioration treatment is II, the deterioration rate at the 3-minute value of the non-pressurized DW is calculated by the following formula. [(I-II) / I] x 100

[0014] When the deterioration rate in the 3-minute value of the non-pressure DW is small, liquid leakage during use of an absorbent article using the water-absorbent resin particles tends to be more effectively suppressed.

[0015] The deterioration rate may be 14% or less, 13% or less, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, or 1% or less. The deterioration rate may be 0%. In other words, the water absorbent resin particles according to one embodiment may not have a change in the 3-minute value of unpressurized DW before and after the deterioration treatment.

[0016] Water-absorbent resin particles exhibiting a deterioration rate of 15% or less can be obtained, for example, by adjusting the crosslink density in the interior and / or surface layer of the water-absorbent resin particles (for example, by uniformly carrying out crosslinking).

[0017] The deterioration rate of non-pressurized DW at 3 minutes can be measured by the method described in the Examples below. In measuring the deterioration rate of non-pressurized DW at 3 minutes, a mixing container having, for example, a mouth inner diameter of 4.1 cm, a body inner diameter of 10.0 cm, and a height of 20.6 cm can be used. The deterioration treatment is carried out using a mixer whose rotation speed and revolution speed can be adjusted to the above range. Examples of mixers include, but are not limited to, a cross rotary mixer (CM-3 type) manufactured by Meiwa Kogyo Co., Ltd. or Tsukasa Kogyo Co., Ltd.

[0018] 4 is a schematic diagram for explaining the direction of rotation and revolution of the mixing vessel. The mixing vessel 300 rotates while the bottom and top surfaces of the mixing vessel 300 are fixed so that the mixing vessel 300 can rotate and revolve. As shown in FIG. 4, the mixing vessel 300 rotates in the direction of a (clockwise direction when viewed from the top surface side of the mixing vessel) around the rotation axis C1, which is the central axis in the height direction of the mixing vessel 300, while revolving in the direction of b around the revolution axis C2, which is located in the center of the height direction of the mixing vessel 300 and perpendicular to the rotation axis C1.

[0019] The 3-minute value of the non-pressurized DW of the water-absorbent resin particles according to the present embodiment (the 3-minute value of the non-pressurized DW before the deterioration treatment) may be, for example, 5 mL / g or more, or 10 mL / g or more, and may be 60 mL / g or less, 55 mL / g or less, 50 mL / g or less, 40 mL / g or less, or 30 mL / g or less.

[0020] The 10-minute value of the non-pressure DW of the water-absorbent resin particles according to the present embodiment (the 10-minute value of the non-pressure DW before the deterioration treatment) may be, for example, 25 mL / g or more, or 35 mL / g or more, and may be 80 mL / g or less, or 70 mL / g or less.

[0021] The 3-minute and 10-minute values ​​of the non-pressurized DW are measured by the method described in the Examples below.

[0022] The water-absorbent resin particles according to the present embodiment may be capable of retaining water, and the liquid to be absorbed may include water. The water-absorbent resin particles according to the present embodiment are excellent in absorbing body fluids such as urine, sweat, and blood (e.g., menstrual blood). The water-absorbent resin particles according to the present embodiment can be used as a constituent component of the absorbent according to the present embodiment.

[0023] The water-absorbent resin particles according to the present embodiment may have a water-retention capacity of physiological saline of 20 g / g or more, 25 g / g or more, 30 g / g or more, 35 g / g or more, more than 40 g / g, or 41 g / g or more. The water-absorbent resin particles according to the present embodiment may have a water-retention capacity of physiological saline of 80 g / g or less, 75 g / g or less, 70 g / g or less, 65 g / g or less, 60 g / g or less, or 55 g / g or less. The water-absorbent resin particles according to the present embodiment may have a water-retention capacity of physiological saline of, for example, 20 to 80 g / g, 30 to 70 g / g, 35 to 60 g / g, or 40 to 55 g / g. The water-retention capacity may be a water-retention capacity at room temperature (25±2°C). The water-retention capacity can be measured by a method described in the examples described later.

[0024] The shape of the water-absorbent resin particles according to the present embodiment may be substantially spherical, crushed, granular, or the like. The water-absorbent resin particles according to the present embodiment may be in a form in which fine particles (primary particles) are aggregated (secondary particles) in addition to a form in which each particle is composed of a single particle. The median particle diameter of the water-absorbent resin particles according to the present embodiment (water-absorbent resin particles before water absorption) is preferably in the following range. The median particle diameter may be 100 μm or more, 140 μm or more, 200 μm or more, 250 μm or more, 300 μm or more, 330 μm or more, or 350 μm or more. The median particle diameter may be 600 μm or less, 550 μm or less, 500 μm or less, 450 μm or less, 400 μm or less, or 380 μm or less. The median particle diameter may be, for example, 100 to 600 μm. The water-absorbent resin particles according to the present embodiment may have a desired particle size distribution when obtained by a production method described later, but the particle size distribution may be adjusted by carrying out an operation such as particle size adjustment using classification with a sieve.

[0025] The water-absorbent resin particles according to the present embodiment may contain, for example, a crosslinked polymer (a crosslinked polymer having a structural unit derived from an ethylenically unsaturated monomer) obtained by polymerizing a monomer containing an ethylenically unsaturated monomer as a polymer particle. That is, the water-absorbent resin particles according to the present embodiment may contain a polymer having a structural unit derived from an ethylenically unsaturated monomer, and may contain polymer particles containing a crosslinked polymer having a structural unit derived from an ethylenically unsaturated monomer. As the ethylenically unsaturated monomer, a water-soluble ethylenically unsaturated monomer may be used. Examples of the polymerization method include reversed-phase suspension polymerization, aqueous solution polymerization, bulk polymerization, and precipitation polymerization. Among these, the reversed-phase suspension polymerization or aqueous solution polymerization is preferable from the viewpoint of ensuring good water absorption characteristics (water retention, etc.) of the obtained water-absorbent resin particles and easy control of the polymerization reaction. In the following, the reversed-phase suspension polymerization is taken as an example to explain the method of polymerizing an ethylenically unsaturated monomer.

[0026] The ethylenically unsaturated monomer is preferably water-soluble, and examples thereof include (meth)acrylic acid and its salts, 2-(meth)acrylamido-2-methylpropanesulfonic acid and its salts, (meth)acrylamide, N,N-dimethyl(meth)acrylamide, 2-hydroxyethyl(meth)acrylate, N-methylol(meth)acrylamide, polyethylene glycol mono(meth)acrylate, N,N-diethylaminoethyl(meth)acrylate, N,N-diethylaminopropyl(meth)acrylate, and diethylaminopropyl(meth)acrylamide. When the ethylenically unsaturated monomer has an amino group, the amino group may be quaternized. The ethylenically unsaturated monomer may be used alone or in combination of two or more kinds. The functional groups of the above-mentioned monomers, such as carboxyl groups and amino groups, may function as functional groups capable of crosslinking in the surface crosslinking step described below.

[0027] Among these, from the viewpoint of industrial availability, the ethylenically unsaturated monomer preferably contains at least one compound selected from the group consisting of (meth)acrylic acid and its salts, acrylamide, methacrylamide, and N,N-dimethylacrylamide, and more preferably contains at least one compound selected from the group consisting of (meth)acrylic acid and its salts, and acrylamide. From the viewpoint of further enhancing water absorption properties (water retention capacity, etc.), the ethylenically unsaturated monomer more preferably contains at least one compound selected from the group consisting of (meth)acrylic acid and its salts. That is, the water absorbent resin particles preferably contain a polymer having at least one structural unit selected from the group consisting of structural units derived from (meth)acrylic acid and structural units derived from salts of (meth)acrylic acid.

[0028] As a monomer for obtaining water-absorbing resin particles, a monomer other than the above-mentioned ethylenically unsaturated monomer may be used. Such a monomer can be used by mixing with an aqueous solution containing the above-mentioned ethylenically unsaturated monomer. The amount of the ethylenically unsaturated monomer used may be 70 to 100 mol%, 80 to 100 mol%, 90 to 100 mol%, 95 to 100 mol%, or 100 mol% based on the total amount of monomers (total amount of monomers for obtaining water-absorbing resin particles. For example, the total amount of monomers that provide structural units of a crosslinked polymer. The same applies below.). Among them, the ratio of (meth)acrylic acid and salts thereof may be 70 to 100 mol%, 80 to 100 mol%, 90 to 100 mol%, 95 to 100 mol%, or 100 mol% based on the total amount of monomers. "Ratio of (meth)acrylic acid and salts thereof" means the ratio of the total amount of (meth)acrylic acid and salts thereof.

[0029] According to the present embodiment, as an example of the water-absorbent resin particles, it is possible to provide water-absorbent resin particles containing a crosslinked polymer having a structural unit derived from an ethylenically unsaturated monomer, the ethylenically unsaturated monomer containing at least one compound selected from the group consisting of (meth)acrylic acid and salts thereof, and the ratio of the (meth)acrylic acid and the salts thereof is 70 to 100 mol % based on the total amount of monomers for obtaining the water-absorbent resin particles.

[0030] The ethylenically unsaturated monomer is usually preferably used as an aqueous solution. The concentration of the ethylenically unsaturated monomer in the aqueous solution containing the ethylenically unsaturated monomer (hereinafter simply referred to as "aqueous monomer solution") is preferably 20% by mass or more and less than the saturated concentration, more preferably 25 to 70% by mass, and even more preferably 30 to 55% by mass. Examples of water used in the aqueous solution include tap water, distilled water, and ion-exchanged water.

[0031] When the ethylenically unsaturated monomer has an acid group, the aqueous monomer solution may be used after neutralizing the acid group with an alkaline neutralizing agent. The degree of neutralization of the ethylenically unsaturated monomer with the alkaline neutralizing agent is preferably 10 to 100 mol %, more preferably 50 to 90 mol %, and even more preferably 60 to 80 mol % of the acid group in the ethylenically unsaturated monomer, from the viewpoint of increasing the osmotic pressure of the resulting water absorbent resin particles and further increasing the water absorption properties (water retention capacity, etc.). Examples of the alkaline neutralizing agent include alkali metal salts such as sodium hydroxide, sodium carbonate, sodium hydrogen carbonate, potassium hydroxide, and potassium carbonate; ammonia, etc. The alkaline neutralizing agent may be used alone or in combination of two or more kinds. The alkaline neutralizing agent may be used in the form of an aqueous solution in order to simplify the neutralization operation. The neutralization of the acid group of the ethylenically unsaturated monomer can be carried out, for example, by dropping an aqueous solution of sodium hydroxide, potassium hydroxide, or the like into the above-mentioned aqueous monomer solution and mixing.

[0032] In the reversed phase suspension polymerization method, an aqueous monomer solution is dispersed in a hydrocarbon dispersion medium in the presence of a surfactant, and an ethylenically unsaturated monomer can be polymerized using a radical polymerization initiator, etc. As the radical polymerization initiator, a water-soluble radical polymerization initiator can be used.

[0033] Examples of the surfactant include nonionic surfactants and anionic surfactants. Examples of the nonionic surfactant include sorbitan fatty acid esters, polyglycerin fatty acid esters, sucrose fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene glycerin fatty acid esters, sorbitol fatty acid esters, polyoxyethylene sorbitol fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, polyoxyethylene castor oil, polyoxyethylene hardened castor oil, alkyl allyl formaldehyde condensed polyoxyethylene ethers, polyoxyethylene polyoxypropylene block copolymers, polyoxyethylene polyoxypropyl alkyl ethers, and polyethylene glycol fatty acid esters. Examples of the anionic surfactant include fatty acid salts, alkyl benzene sulfonates, alkyl methyl taurate salts, polyoxyethylene alkyl phenyl ether sulfate salts, polyoxyethylene alkyl ether sulfonates, polyoxyethylene alkyl ether phosphates, and polyoxyethylene alkyl allyl ether phosphates. The surfactants may be used alone or in combination of two or more.

[0034] From the viewpoints of obtaining a good W / O type reverse phase suspension state, easily obtaining water-absorbent resin particles having a suitable particle size, and being easily available industrially, it is preferable that the surfactant contains at least one compound selected from the group consisting of sorbitan fatty acid esters, polyglycerin fatty acid esters, and sucrose fatty acid esters. From the viewpoints of easily obtaining an appropriate particle size distribution of the water-absorbent resin particles, and easily improving the water-absorption characteristics (water retention capacity, etc.) of the water-absorbent resin particles and the performance of the absorbent article using the same, it is preferable that the surfactant contains a sucrose fatty acid ester, and more preferably a sucrose stearate ester.

[0035] The amount of the surfactant used is preferably 0.05 to 10 parts by mass, more preferably 0.08 to 5 parts by mass, and even more preferably 0.1 to 3 parts by mass, per 100 parts by mass of the aqueous monomer solution, from the viewpoint of obtaining a sufficient effect relative to the amount used and from the viewpoint of economical efficiency.

[0036] In the reversed-phase suspension polymerization, a polymeric dispersant may be used in combination with the above-mentioned surfactant. Examples of the polymeric dispersant include maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-modified EPDM (ethylene-propylene-diene-terpolymer), maleic anhydride-modified polybutadiene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, maleic anhydride-butadiene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, ethylene-acrylic acid copolymer, ethyl cellulose, ethyl hydroxyethyl cellulose, etc. The polymeric dispersant may be used alone or in combination of two or more. As the polymer dispersant, from the viewpoint of excellent dispersion stability of the monomer, at least one selected from the group consisting of maleic anhydride modified polyethylene, maleic anhydride modified polypropylene, maleic anhydride modified ethylene-propylene copolymer, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, and oxidized ethylene-propylene copolymer is preferable.

[0037] The amount of the polymer dispersant used is preferably 0.05 to 10 parts by mass, more preferably 0.08 to 5 parts by mass, and even more preferably 0.1 to 3 parts by mass, per 100 parts by mass of the aqueous monomer solution, from the viewpoint of obtaining a sufficient effect relative to the amount used and from the viewpoint of economical efficiency.

[0038] The hydrocarbon dispersion medium may contain at least one compound selected from the group consisting of chain aliphatic hydrocarbons having 6 to 8 carbon atoms and alicyclic hydrocarbons having 6 to 8 carbon atoms. Examples of the hydrocarbon dispersion medium include chain aliphatic hydrocarbons such as n-hexane, n-heptane, 2-methylhexane, 3-methylhexane, 2,3-dimethylpentane, 3-ethylpentane, and n-octane; alicyclic hydrocarbons such as cyclohexane, methylcyclohexane, cyclopentane, methylcyclopentane, trans-1,2-dimethylcyclopentane, cis-1,3-dimethylcyclopentane, and trans-1,3-dimethylcyclopentane; and aromatic hydrocarbons such as benzene, toluene, and xylene. The hydrocarbon dispersion medium may be used alone or in combination of two or more kinds.

[0039] The hydrocarbon dispersion medium may contain at least one selected from the group consisting of n-heptane and cyclohexane, from the viewpoint of industrial availability and stable quality. From the same viewpoint, the mixture of the above-mentioned hydrocarbon dispersion medium may be, for example, commercially available Exxolheptane (manufactured by ExxonMobil Corp.: containing 75 to 85% of n-heptane and isomeric hydrocarbons).

[0040] The amount of the hydrocarbon dispersion medium used is preferably 30 to 1000 parts by mass, more preferably 40 to 500 parts by mass, and even more preferably 50 to 400 parts by mass, relative to 100 parts by mass of the aqueous monomer solution, from the viewpoint of adequately removing the heat of polymerization and easily controlling the polymerization temperature. When the amount of the hydrocarbon dispersion medium used is 30 parts by mass or more, the polymerization temperature tends to be easily controlled. When the amount of the hydrocarbon dispersion medium used is 1000 parts by mass or less, the polymerization productivity tends to be improved, which is economical.

[0041] The radical polymerization initiator is preferably water-soluble, and examples thereof include persulfates such as potassium persulfate, ammonium persulfate, and sodium persulfate; peroxides such as methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, di-t-butyl peroxide, t-butyl cumyl peroxide, t-butyl peroxyacetate, t-butyl peroxyisobutyrate, t-butyl peroxypivalate, and hydrogen peroxide; 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(N-phenylamidino)propane] dihydrochloride, and 2,2' 2,2'-azobis[2-(N-allylamidino)propane]dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane}dihydrochloride, 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], 4,4'-azobis(4-cyanovaleric acid) and other azo compounds. The radical polymerization initiator may be used alone or in combination of two or more. The radical polymerization initiator is preferably at least one selected from the group consisting of potassium persulfate, ammonium persulfate, sodium persulfate, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, and 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane} dihydrochloride, and more preferably potassium persulfate, ammonium persulfate, or sodium persulfate.

[0042] The amount of the radical polymerization initiator used may be 0.05 to 10 millimoles per mole of the ethylenically unsaturated monomer. When the amount of the radical polymerization initiator used is 0.05 millimoles or more, the polymerization reaction does not take a long time and is efficient. When the amount of the radical polymerization initiator used is 10 millimoles or less, it is easy to suppress the occurrence of a rapid polymerization reaction.

[0043] The above-mentioned radical polymerization initiators can also be used as redox polymerization initiators in combination with reducing agents such as sodium sulfite, sodium hydrogen sulfite, ferrous sulfate, and L-ascorbic acid.

[0044] In the polymerization reaction, the aqueous monomer solution used for the polymerization may contain a chain transfer agent, such as hypophosphites, thiols, thiolic acids, secondary alcohols, and amines.

[0045] In order to control the particle size of the water-absorbent resin particles, the monomer aqueous solution used for polymerization may contain a thickener. Examples of the thickener include hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, carboxymethyl cellulose, polyethylene glycol, polyacrylamide, polyethyleneimine, dextrin, sodium alginate, polyvinyl alcohol, polyvinylpyrrolidone, and polyethylene oxide. If the stirring speed during polymerization is the same, the higher the viscosity of the monomer aqueous solution, the larger the median particle size of the resulting particles tends to be.

[0046] During polymerization, internal crosslinking may occur due to self-crosslinking, but crosslinking may also be performed by using an internal crosslinking agent. The use of an internal crosslinking agent makes it easier to control the water absorption characteristics (water retention amount, etc.) of the water-absorbent resin particles. The internal crosslinking agent is usually added to the reaction solution during the polymerization reaction. Examples of the internal crosslinking agent include di- or tri(meth)acrylic acid esters of polyols such as ethylene glycol, propylene glycol, trimethylolpropane, glycerin, polyoxyethylene glycol, polyoxypropylene glycol, and polyglycerin; unsaturated polyesters obtained by reacting the above-mentioned polyols with unsaturated acids (maleic acid, fumaric acid, and the like); bis(meth)acrylamides such as N,N'-methylenebis(meth)acrylamide; di- or tri(meth)acrylic acid esters obtained by reacting polyepoxides with (meth)acrylic acid; di(meth)acrylic acid carbamyl esters obtained by reacting polyisocyanates (tolylene diisocyanate, hexamethylene diisocyanate, and the like) with hydroxyethyl (meth)acrylate; compounds having two or more polymerizable unsaturated groups, such as allylated starch, allylated cellulose, diallyl phthalate, N,N',N"-triallyl isocyanurate, and divinylbenzene; Examples of the internal crosslinking agent include polyglycidyl compounds such as glyceryl diglycidyl ether, (poly)propylene glycol diglycidyl ether, (poly)glycerin diglycidyl ether, (poly)glycerin triglycidyl ether, (poly)propylene glycol polyglycidyl ether, and polyglycerol polyglycidyl ether; haloepoxy compounds such as epichlorohydrin, epibromohydrin, and α-methylepichlorohydrin; and compounds having two or more reactive functional groups such as isocyanate compounds (2,4-tolylene diisocyanate, hexamethylene diisocyanate, etc.). The internal crosslinking agent may be used alone or in combination of two or more. As the internal crosslinking agent, a polyglycidyl compound is preferred, a diglycidyl ether compound is more preferred, and at least one selected from the group consisting of (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, and (poly)glycerin diglycidyl ether is even more preferred.

[0047] The amount of the internal crosslinking agent used is preferably 30 mmol or less, more preferably 0.01 to 10 mmol, even more preferably 0.012 to 5 mmol, particularly preferably 0.015 to 1 mmol, extremely preferably 0.02 to 0.1 mmol, and extremely preferably 0.025 to 0.06 mmol, per mole of the ethylenically unsaturated monomer, from the viewpoint that the water-soluble property is suppressed by moderate crosslinking of the obtained polymer and a sufficient water absorption amount is easily obtained.

[0048] An ethylenically unsaturated monomer, a radical polymerization initiator, a surfactant, a polymeric dispersant, a hydrocarbon dispersion medium, etc. (and an internal crosslinking agent, if necessary) are mixed and heated with stirring to carry out reverse phase suspension polymerization in a water-in-oil system.

[0049] When performing reversed-phase suspension polymerization, an aqueous monomer solution containing an ethylenically unsaturated monomer is dispersed in a hydrocarbon dispersion medium in the presence of a surfactant (and a polymeric dispersant, if necessary). In this case, the timing of adding the surfactant, polymeric dispersant, etc. may be either before or after the addition of the aqueous monomer solution, so long as it is before the start of the polymerization reaction.

[0050] Among them, from the viewpoint of easily reducing the amount of the hydrocarbon dispersion medium remaining in the obtained water absorbent resin, it is preferable to disperse an aqueous monomer solution in a hydrocarbon dispersion medium having a polymeric dispersant dispersed therein, and then further disperse a surfactant therein, and then carry out polymerization.

[0051] The reversed-phase suspension polymerization can be carried out in one stage or in multiple stages of two or more stages. From the viewpoint of increasing productivity, the reversed-phase suspension polymerization is preferably carried out in two to three stages.

[0052] When performing reversed-phase suspension polymerization in two or more stages, after performing reversed-phase suspension polymerization in the first stage, an ethylenically unsaturated monomer is added to the reaction mixture obtained in the polymerization reaction in the first stage and mixed, and reversed-phase suspension polymerization in the second stage and thereafter may be performed in the same manner as in the first stage. In the reversed-phase suspension polymerization in each stage after the second stage, it is preferable to perform reversed-phase suspension polymerization by adding the above-mentioned radical polymerization initiator and / or internal crosslinking agent in addition to the ethylenically unsaturated monomer within the range of the molar ratio of each component to the above-mentioned ethylenically unsaturated monomer based on the amount of the ethylenically unsaturated monomer added during the reversed-phase suspension polymerization in each stage after the second stage. In addition, in the reversed-phase suspension polymerization in each stage after the second stage, an internal crosslinking agent may be used as necessary. When an internal crosslinking agent is used, it is preferable to perform reversed-phase suspension polymerization by adding the above-mentioned radical polymerization initiator and / or internal crosslinking agent within the range of the molar ratio of each component to the above-mentioned ethylenically unsaturated monomer based on the amount of the ethylenically unsaturated monomer to be provided to each stage.

[0053] The temperature of the polymerization reaction varies depending on the radical polymerization initiator used, but from the viewpoint of quickly progressing the polymerization and shortening the polymerization time to improve economic efficiency and easily removing the polymerization heat to smoothly carry out the reaction, the temperature is preferably 20 to 150°C, more preferably 40 to 120°C. The reaction time is usually 0.5 to 4 hours. The end of the polymerization reaction can be confirmed, for example, by the cessation of the temperature rise in the reaction system. As a result, the polymer of the ethylenically unsaturated monomer is usually obtained in the form of a hydrogel.

[0054] After polymerization, a post-polymerization crosslinking agent may be added to the obtained hydrogel polymer and the resulting polymer may be heated to crosslink the polymer. By crosslinking the polymer after polymerization, the degree of crosslinking of the hydrogel polymer may be increased, and the water absorption properties (water retention, etc.) may be further improved.

[0055] Examples of post-polymerization crosslinking agents include polyols such as ethylene glycol, propylene glycol, 1,4-butanediol, trimethylolpropane, glycerin, polyoxyethylene glycol, polyoxypropylene glycol, and polyglycerin; compounds having two or more epoxy groups such as (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, and (poly)glycerin diglycidyl ether; haloepoxy compounds such as epichlorohydrin, epibromohydrin, and α-methylepichlorohydrin; compounds having two or more isocyanate groups such as 2,4-tolylene diisocyanate and hexamethylene diisocyanate; oxazoline compounds such as 1,2-ethylenebisoxazoline; carbonate compounds such as ethylene carbonate; and hydroxyalkylamide compounds such as bis[N,N-di(β-hydroxyethyl)]adipamide. Among these, polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)glycerin diglycidyl ether, (poly)glycerin triglycidyl ether, (poly)propylene glycol polyglycidyl ether, polyglycerol polyglycidyl ether, etc. are preferred. The crosslinking agents may be used alone or in combination of two or more.

[0056] From the viewpoint of easily obtaining suitable water absorption characteristics (water retention amount, etc.), the amount of the crosslinking agent after polymerization is preferably 30 mmol or less, more preferably 10 mmol or less, still more preferably 0.01 to 5 mmol, particularly preferably 0.012 to 1 mmol, extremely preferably 0.015 to 0.1 mmol, and very preferably 0.02 to 0.05 mmol, per mole of the ethylenically unsaturated monomer.

[0057] The timing of adding the crosslinking agent after polymerization may be after the polymerization of the ethylenically unsaturated monomer used in the polymerization, and in the case of multi-stage polymerization, it is preferable to add it after the multi-stage polymerization. In addition, taking into consideration heat generation during and after polymerization, retention due to process delay, opening of the system when the crosslinking agent is added, and fluctuation in moisture due to addition of water accompanying the addition of the crosslinking agent, the crosslinking agent after polymerization is preferably added in the range of [moisture content immediately after polymerization ±3% by mass] from the viewpoint of moisture content (described later).

[0058] Subsequently, the obtained hydrogel polymer is dried to remove water, thereby obtaining polymer particles (e.g., polymer particles containing a polymer having a structural unit derived from an ethylenically unsaturated monomer). Examples of the drying method include (a) a method in which the hydrogel polymer is dispersed in a hydrocarbon dispersion medium and then heated from the outside to perform azeotropic distillation, and the hydrocarbon dispersion medium is refluxed to remove water, (b) a method in which the hydrogel polymer is removed by decantation and dried under reduced pressure, and (c) a method in which the hydrogel polymer is filtered through a filter and dried under reduced pressure. Among these, the method (a) is preferably used because of the simplicity of the production process.

[0059] The particle size of the water-absorbent resin particles can be adjusted by adjusting the rotation speed of the agitator during the polymerization reaction, or by adding a flocculant to the system after the polymerization reaction or at the beginning of drying. By adding a flocculant, the particle size of the obtained water-absorbent resin particles can be increased. As the flocculant, an inorganic flocculant can be used. Examples of inorganic flocculants (for example, powdered inorganic flocculants) include silica, zeolite, bentonite, aluminum oxide, talc, titanium dioxide, kaolin, clay, and hydrotalcite. From the viewpoint of excellent flocculation effect, the flocculant is preferably at least one selected from the group consisting of silica, aluminum oxide, talc, and kaolin.

[0060] In the reversed-phase suspension polymerization, the method of adding the flocculant is preferably a method in which the flocculant is previously dispersed in the same type of hydrocarbon dispersion medium as that used in the polymerization or in water, and then mixed under stirring into the hydrocarbon dispersion medium containing the hydrous gel polymer.

[0061] The amount of the flocculant added is preferably 0.001 to 1 part by mass, more preferably 0.005 to 0.5 parts by mass, and even more preferably 0.01 to 0.2 parts by mass, relative to 100 parts by mass of the ethylenically unsaturated monomer used in the polymerization. By setting the amount of the flocculant added within the above range, water absorbent resin particles having a desired particle size distribution can be easily obtained.

[0062] In the production of water-absorbent resin particles, it is preferable to perform surface crosslinking of the surface portion (surface and surface vicinity) of the hydrogel polymer using a surface crosslinking agent in the drying step (water removal step) or a subsequent step. By performing surface crosslinking, it is easy to control the water absorption characteristics (water retention amount, etc.) of the water-absorbent resin particles. It is preferable to perform surface crosslinking at a timing when the hydrogel polymer has a specific water content. The timing of surface crosslinking is preferably when the water content of the hydrogel polymer is 5 to 50% by mass, more preferably when it is 10 to 40% by mass, and even more preferably when it is 15 to 35% by mass. The water content (mass%) of the hydrogel polymer is calculated by the following formula. Moisture content=[Ww / (Ww+Ws)]×100 Ww: The water content of the hydrous gel polymer, calculated by subtracting the water content discharged outside the system in the drying process from the water content contained in the aqueous monomer solution before polymerization in all polymerization processes, plus the water content used as necessary when mixing a flocculant, surface cross-linking agent, etc. Ws: The solid content calculated from the amounts of the ethylenically unsaturated monomer, crosslinking agent, initiator, and other materials that constitute the hydrous gel polymer.

[0063] Examples of the surface cross-linking agent include compounds having two or more reactive functional groups. Examples of the surface cross-linking agent include polyols such as ethylene glycol, propylene glycol, 1,4-butanediol, trimethylolpropane, glycerin, polyoxyethylene glycol, polyoxypropylene glycol, and polyglycerin; polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)glycerin diglycidyl ether, (poly)glycerin triglycidyl ether, trimethylolpropane triglycidyl ether, (poly)propylene glycol polyglycidyl ether, and (poly)glycerol polyglycidyl ether; epichlorohydrin, epibromohydrin, α-methylepichlorohydrin, and the like. Examples of the surface crosslinking agent include haloepoxy compounds such as 2,4-tolylene diisocyanate and hexamethylene diisocyanate; oxetane compounds such as 3-methyl-3-oxetanemethanol, 3-ethyl-3-oxetanemethanol, 3-butyl-3-oxetanemethanol, 3-methyl-3-oxetaneethanol, 3-ethyl-3-oxetaneethanol, and 3-butyl-3-oxetaneethanol; oxazoline compounds such as 1,2-ethylenebisoxazoline; carbonate compounds such as ethylene carbonate; and hydroxyalkylamide compounds such as bis[N,N-di(β-hydroxyethyl)]adipamide. The surface crosslinking agent may be used alone or in combination of two or more. The surface cross-linking agent is preferably a polyglycidyl compound, and more preferably at least one selected from the group consisting of (poly)ethylene glycol diglycidyl ether, (poly)glycerin diglycidyl ether, (poly)glycerin triglycidyl ether, (poly)propylene glycol polyglycidyl ether, and polyglycerol polyglycidyl ether.

[0064] The amount of the surface crosslinking agent used is preferably 0.01 to 20 mmol, more preferably 0.05 to 10 mmol, still more preferably 0.1 to 5 mmol, particularly preferably 0.15 to 1 mmol, and extremely preferably 0.2 to 0.5 mmol, relative to 1 mol of the ethylenically unsaturated monomer used in the polymerization, from the viewpoint of easily obtaining suitable water absorption characteristics (water retention amount, etc.).

[0065] After the surface cross-linking, the water and the hydrocarbon dispersion medium are distilled off by a known method, and the resulting product is dried under heating and reduced pressure, thereby obtaining polymer particles that are a surface-cross-linked, dried product.

[0066] The polymerization reaction can be carried out using various agitators having an agitating blade. As the agitating blade, a flat blade, a lattice blade, a paddle blade, a propeller blade, an anchor blade, a turbine blade, a Pfaudle blade, a ribbon blade, a full zone blade, a Max Blend blade, etc. can be used. The flat blade has a shaft (agitating shaft) and a flat plate part (agitating part) arranged around the shaft. The flat plate part may have a slit or the like. When a flat blade is used as the agitating blade, the crosslinking reaction in the polymer particles is easily carried out uniformly, and the deterioration rate at the 3-minute value of the unpressurized DW is easily adjusted to a suitable range while maintaining the water absorption characteristics such as the water retention capacity.

[0067] The water-absorbent resin particles according to the present embodiment may further include additional components such as a gel stabilizer, a metal chelating agent (ethylenediaminetetraacetic acid and its salts, diethylenetriaminepentaacetic acid and its salts, such as diethylenetriaminepentaacetic acid pentasodium salt, etc.), a flow improver (lubricant), etc. The additional components may be disposed inside the polymer particles, on the surface of the polymer particles, or both.

[0068] The water-absorbing resin particles may include a plurality of inorganic particles arranged on the surface of the polymer particles. For example, the inorganic particles can be arranged on the surface of the polymer particles by mixing the polymer particles with the inorganic particles. The inorganic particles may be silica particles such as amorphous silica.

[0069] When the water-absorbent resin particles include inorganic particles arranged on the surface of the polymer particles, the content of the inorganic particles may be in the following ranges based on the total mass of the polymer particles. The content of the inorganic particles may be 0.05% by mass or more, 0.1% by mass or more, 0.15% by mass or more, or 0.2% by mass or more. The content of the inorganic particles may be 5.0% by mass or less, 3.0% by mass or less, 1.0% by mass or less, or 0.5% by mass or less.

[0070] The inorganic particles here usually have a size that is smaller than the size of the polymer particles. For example, the average particle size of the inorganic particles may be 0.1 to 50 μm, 0.5 to 30 μm, or 1 to 20 μm. The average particle size can be measured by a pore electrical resistance method or a laser diffraction / scattering method depending on the characteristics of the particles.

[0071] The absorbent according to the present embodiment contains the water-absorbing resin particles according to the present embodiment. The absorbent according to the present embodiment may contain fibrous material, for example, may be a mixture containing water-absorbing resin particles and fibrous material. The absorbent may have a configuration in which water-absorbing resin particles and fibrous material are uniformly mixed, a configuration in which water-absorbing resin particles are sandwiched between fibrous material formed in a sheet or layer, or other configurations.

[0072] Examples of the fibrous material include finely ground wood pulp, cotton, cotton linters, rayon, cellulosic fibers such as cellulose acetate, synthetic fibers such as polyamide, polyester, polyolefin, and mixtures of these fibers. The average fiber length of the fibrous material is usually 0.1 to 10 mm, and may be 0.5 to 5 mm. The fibrous material may be used alone or in combination of two or more kinds. As the fibrous material, hydrophilic fibers may be used.

[0073] In order to improve the shape retention of the absorbent before and during use, an adhesive binder may be added to the fibrous material to bond the fibers together. Examples of the adhesive binder include heat-fusible synthetic fibers, hot melt adhesives, adhesive emulsions, etc. The adhesive binder may be used alone or in combination of two or more kinds.

[0074] Examples of heat-fusible synthetic fibers include fully melted binders such as polyethylene, polypropylene, and ethylene-propylene copolymers; non-fully melted binders having a side-by-side or core-sheath structure of polypropylene and polyethylene, etc. In the above-mentioned non-fully melted binders, only the polyethylene portion can be heat-fusible.

[0075] Examples of hot melt adhesives include mixtures of base polymers such as ethylene-vinyl acetate copolymers, styrene-isoprene-styrene block copolymers, styrene-butadiene-styrene block copolymers, styrene-ethylene-butylene-styrene block copolymers, styrene-ethylene-propylene-styrene block copolymers, and amorphous polypropylene with tackifiers, plasticizers, antioxidants, and the like.

[0076] The adhesive emulsion may be, for example, a polymer of at least one monomer selected from the group consisting of methyl methacrylate, styrene, acrylonitrile, 2-ethylhexyl acrylate, butyl acrylate, butadiene, ethylene, and vinyl acetate.

[0077] The absorbent body according to the present embodiment may contain inorganic powder (e.g., amorphous silica), a deodorant, an antibacterial agent, a pigment, a dye, a fragrance, an adhesive, etc. When the water-absorbent resin particles contain inorganic particles, the absorbent body may contain inorganic powder in addition to the inorganic particles in the water-absorbent resin particles.

[0078] The absorbent body according to this embodiment may be, for example, in a sheet shape. The thickness of the absorbent body (for example, the thickness of the sheet-shaped absorbent body) may be 0.1 to 20 mm or 0.3 to 15 mm.

[0079] The content of the water-absorbent resin particles in the absorbent body may be 2 to 100 mass %, 10 to 80 mass %, or 20 to 60 mass % based on the total of the water-absorbent resin particles and fibrous material, from the viewpoint of easily obtaining sufficient absorption properties.

[0080] The content of water-absorbent resin particles in the absorbent body is set at 1 / 3 of the absorbent body from the viewpoint of obtaining sufficient absorption characteristics. 2 The content of the fibrous material in the absorbent body is preferably 100 to 1000 g, more preferably 150 to 800 g, and even more preferably 200 to 700 g per m of the absorbent body from the viewpoint of easily obtaining sufficient absorption properties. 2 The weight is preferably 50 to 800 g, more preferably 100 to 600 g, and even more preferably 150 to 500 g.

[0081] The absorbent article according to the present embodiment includes the absorbent body according to the present embodiment. Other components of the absorbent article according to the present embodiment include a core wrap that maintains the shape of the absorbent body and prevents the components of the absorbent body from falling off and flowing; a liquid-permeable sheet that is disposed on the outermost side of the side into which the liquid to be absorbed penetrates; and a liquid-impermeable sheet that is disposed on the outermost side of the side opposite to the side into which the liquid to be absorbed penetrates. Examples of absorbent articles include diapers (e.g., paper diapers), toilet training pants, incontinence pads, sanitary materials (sanitary napkins, tampons, etc.), sweat pads, pet sheets, parts for simple toilets, and animal waste treatment materials.

[0082] Fig. 1 is a cross-sectional view showing an example of an absorbent article. The absorbent article 100 shown in Fig. 1 includes an absorbent body 10, core wraps 20a and 20b, a liquid-permeable sheet 30, and a liquid-impermeable sheet 40. In the absorbent article 100, the liquid-impermeable sheet 40, the core wrap 20b, the absorbent body 10, the core wrap 20a, and the liquid-permeable sheet 30 are laminated in this order. In Fig. 1, there are some parts shown as having gaps between the members, but the members may be in close contact with each other without the presence of such gaps.

[0083] The absorbent body 10 includes water-absorbent resin particles 10a according to the present embodiment and a fiber layer 10b containing fibrous material. The water-absorbent resin particles 10a are dispersed in the fiber layer 10b.

[0084] The core wrap 20a is disposed on one side of the absorbent body 10 (upper side of the absorbent body 10 in FIG. 1) in contact with the absorbent body 10. The core wrap 20b is disposed on the other side of the absorbent body 10 (lower side of the absorbent body 10 in FIG. 1) in contact with the absorbent body 10. The absorbent body 10 is disposed between the core wrap 20a and the core wrap 20b. Examples of the core wraps 20a and 20b include tissue, nonwoven fabric, woven fabric, synthetic resin film having liquid permeable holes, and net-like sheet having mesh. The core wrap 20a and the core wrap 20b have a main surface of the same size as that of the absorbent body 10, for example.

[0085] The liquid-permeable sheet 30 is disposed on the outermost side of the absorbent article 100, on which the liquid to be absorbed penetrates. The liquid-permeable sheet 30 is disposed on the core wrap 20a in a state of contact with the core wrap 20a. Examples of the liquid-permeable sheet 30 include nonwoven fabrics and porous sheets made of synthetic resins such as polyethylene, polypropylene, polyester, and polyamide. The liquid-impermeable sheet 40 is disposed on the outermost side of the absorbent article 100, on the opposite side to the liquid-permeable sheet 30. The liquid-impermeable sheet 40 is disposed below the core wrap 20b in a state of contact with the core wrap 20b. Examples of the liquid-impermeable sheet 40 include sheets made of synthetic resins such as polyethylene, polypropylene, and polyvinyl chloride, and sheets made of composite materials of these synthetic resins and nonwoven fabrics. The liquid-permeable sheet 30 and the liquid-impermeable sheet 40 have, for example, a main surface that is wider than the main surface of the absorbent body 10, and the outer edges of the liquid-permeable sheet 30 and the liquid-impermeable sheet 40 extend around the absorbent body 10 and the core wraps 20a, 20b.

[0086] The size relationship between the absorbent body 10, the core wraps 20a, 20b, the liquid permeable sheet 30, and the liquid impermeable sheet 40 is not particularly limited and is adjusted as appropriate depending on the application of the absorbent article, etc. Furthermore, the method of maintaining the shape of the absorbent body 10 using the core wraps 20a, 20b is not particularly limited, and the absorbent body may be wrapped with multiple core wraps as shown in Fig. 1, or may be wrapped with one core wrap.

[0087] The absorbent may be bonded to the top sheet. When the absorbent is sandwiched or covered by a core wrap, it is preferable that at least the core wrap and the top sheet are bonded, and it is more preferable that the core wrap and the top sheet are bonded and the core wrap and the absorbent are bonded. Examples of the method of bonding the absorbent include a method of applying a hot melt adhesive to the top sheet in a stripe or spiral pattern at a predetermined interval in the width direction and bonding it; a method of bonding using a water-soluble binder such as starch, carboxymethyl cellulose, polyvinyl alcohol, polyvinylpyrrolidone, or other water-soluble polymers. In addition, when the absorbent contains a heat-fusible synthetic fiber, a method of bonding by heat fusion of the heat-fusible synthetic fiber may be adopted.

[0088] According to the present embodiment, a method for absorbing liquid using the water-absorbent resin particles, absorbent body, or absorbent article according to the present embodiment can be provided. The method for absorbing liquid according to the present embodiment includes a step of contacting the water-absorbent resin particles, absorbent body, or absorbent article according to the present embodiment with a liquid to be absorbed.

[0089] According to the present embodiment, there is provided a method for suppressing liquid leakage in an absorbent article, which method uses the water-absorbent resin particles, absorbent body, or absorbent article according to the present embodiment. The method for suppressing liquid leakage according to the present embodiment includes an adjustment step of adjusting the deterioration rate at 3-minute value of unpressurized DW measured by the above-mentioned procedures (1) to (3) for the water-absorbent resin particles according to the present embodiment. In the adjustment step, the deterioration rate at 3-minute value of unpressurized DW can be adjusted to each of the above-mentioned ranges (for example, 15% or less).

[0090] According to the present embodiment, it is possible to provide a method for producing water-absorbent resin particles, which includes a selection step of selecting water-absorbent resin particles based on the deterioration rate at 3-minute value of non-pressure DW measured by the above-mentioned procedures (1) to (3) for the water-absorbent resin particles according to the present embodiment. In the selection step, the deterioration rate at 3-minute value of non-pressure DW can be adjusted to each of the above-mentioned ranges (for example, 15% or less).

[0091] According to this embodiment, it is possible to provide a method for manufacturing an absorbent body using water-absorbent resin particles obtained by the above-mentioned method for manufacturing water-absorbent resin particles. The method for manufacturing an absorbent body according to this embodiment includes a particle manufacturing step of obtaining water-absorbent resin particles by the above-mentioned method for manufacturing water-absorbent resin particles. The method for manufacturing an absorbent body according to this embodiment may include a step of mixing water-absorbent resin particles and fibrous material after the particle manufacturing step. According to this embodiment, it is possible to provide a method for manufacturing an absorbent article using an absorbent body obtained by the above-mentioned method for manufacturing an absorbent body. The method for manufacturing an absorbent article according to this embodiment includes an absorbent body manufacturing step of obtaining an absorbent body by the above-mentioned method for manufacturing an absorbent body. The method for manufacturing an absorbent article according to this embodiment may include a step of obtaining an absorbent article using the absorbent body and other constituent members of the absorbent article after the absorbent body manufacturing step, and in this step, for example, the absorbent article is obtained by stacking the absorbent body and other constituent members of the absorbent article on each other. EXAMPLES

[0092] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples.

[0093] 1. Preparation of Water-absorbent Resin Particles Example 1 A round-bottomed cylindrical separable flask with an inner diameter of 11 cm and an internal volume of 2 L was prepared, equipped with a reflux condenser, a dropping funnel, a nitrogen gas introduction tube, and a stirrer. A stirring blade 200, the outline of which is shown in FIG. 2, was attached to the stirrer. The stirring blade 200 has a shaft 200a and a flat plate portion 200b. The flat plate portion 200b is welded to the shaft 200a and has a curved tip. The flat plate portion 200b has four slits S extending along the axial direction of the shaft 200a. The four slits S are arranged in the width direction of the flat plate portion 200b, with the width of the two inner slits S being 1 cm and the width of the two outer slits S being 0.5 cm. The length of the flat plate portion 200b is about 10 cm, and the width of the flat plate portion 200b is about 6 cm. 293 g of n-heptane and 0.736 g of dispersant (maleic anhydride modified ethylene-propylene copolymer, Mitsui Chemicals, Inc., Hiwax 1105A) were mixed in the prepared separable flask. The mixture in the separable flask was heated to 80°C while being stirred with a stirrer, thereby dissolving the dispersant in n-heptane. The formed solution was cooled to 50°C.

[0094] On the other hand, 92.0g (1.03 mol) of 80.5% by mass acrylic acid aqueous solution was placed in a 300mL beaker as a water-soluble ethylenically unsaturated monomer, and 147.7g of 20.9% by mass sodium hydroxide aqueous solution was added dropwise while cooling from the outside to neutralize 75 mol%. Then, 0.092g of hydroxyethyl cellulose (Sumitomo Seika Chemicals Co., Ltd., HEC AW-15F) as a thickener, 0.0648g (0.272 mmol) of sodium persulfate as a water-soluble radical polymerization initiator, and 0.0156g (0.090 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were added and dissolved in the beaker to prepare the first aqueous solution.

[0095] The aqueous solution prepared above was added to a separable flask and stirred for 10 minutes. Separately, 0.736 g of sucrose stearate (Mitsubishi Chemical Foods Corporation, Ryoto Sugar Ester S-370, HLB: 3) was dissolved as a surfactant in 6.62 g of n-heptane by heating to obtain a surfactant solution. The surfactant solution was added to the flask, and the inside of the system was thoroughly replaced with nitrogen while stirring at a stirrer speed of 350 rpm. Thereafter, the flask was immersed in a water bath at 70°C to raise the temperature, and polymerization was carried out for 60 minutes to obtain a first-stage polymerization slurry liquid.

[0096] On the other hand, 128.8g (1.44 mol) of 80.5% by mass acrylic acid aqueous solution was placed in another 500mL beaker as a water-soluble ethylenically unsaturated monomer, and 159.0g of 27% by mass sodium hydroxide aqueous solution was added dropwise while cooling from the outside to perform 75 mol% neutralization. After that, 0.0907g (0.381 mmol) of sodium persulfate as a water-soluble radical polymerization initiator and 0.0129g (0.074 mmol) of ethylene glycol diglycidyl ether as an internal crosslinking agent were added and dissolved in the beaker to prepare the second aqueous solution.

[0097] The contents of the separable flask were cooled to 25° C. while stirring at a stirrer speed of 650 rpm, and the entire amount of the second-stage aqueous liquid was added to the first-stage polymerization slurry liquid, and the system was purged with nitrogen for 30 minutes. Thereafter, the flask was again immersed in a 70° C. water bath to raise the temperature, and a polymerization reaction was carried out for 60 minutes to obtain a hydrous gel polymer.

[0098] 0.589g of 45% by mass of pentasodium diethylenetriamine pentacetate aqueous solution was added to the hydrous gel polymer after the second-stage polymerization under stirring. Then, the flask was immersed in an oil bath set at 125°C, and 254.5g of water was extracted from the system by azeotropic distillation of n-heptane and water while refluxing n-heptane. Then, 4.42g (0.507mmol) of 2% by mass of ethylene glycol diglycidyl ether aqueous solution was added to the flask as a surface crosslinking agent, and the mixture was kept at 83°C for 2 hours.

[0099] Then, n-heptane was evaporated at 125°C to dry the mixture, thereby obtaining polymer particles (dried product). The polymer particles were passed through a sieve with an opening of 850 μm, and 0.5% by mass of amorphous silica (Oriental Silicas Corporation, Toxil NP-S) was mixed with the polymer particles, thereby obtaining 231.8 g of water-absorbing resin particles containing amorphous silica. The median particle diameter of the water-absorbing resin particles was 368 μm.

[0100] Example 2 In the preparation of the first-stage aqueous liquid, 0.010g (0.057mmol) of ethylene glycol diglycidyl ether was added as an internal crosslinking agent, in the preparation of the second-stage aqueous liquid, 0.0116g (0.067mmol) of ethylene glycol diglycidyl ether was added as an internal crosslinking agent, the amount of water extracted by azeotropic distillation of n-heptane and water was set to 257.2g, and 0.2% by mass of amorphous silica was mixed with the polymer particles in the same manner as in Example 1, to obtain 231.2g of water-absorbent resin particles. The median particle diameter of the water-absorbent resin particles was 359μm.

[0101] Example 3 In the preparation of the first-stage aqueous liquid, 0.010g (0.057mmol) of ethylene glycol diglycidyl ether was added as an internal crosslinking agent, the rotation speed of the stirrer when obtaining the first-stage polymerization slurry liquid was changed to 425rpm, in the preparation of the second-stage aqueous liquid, 0.0116g (0.067mmol) of ethylene glycol diglycidyl ether was added as an internal crosslinking agent, the amount of water extracted by azeotropic distillation of n-heptane and water was set to 271.0g, and 0.2% by mass of amorphous silica was mixed with the polymer particles, except that 229.0g of water-absorbent resin particles were obtained in the same manner as in Example 1. The median particle diameter of the water-absorbent resin particles was 360μm.

[0102] Example 4 In the preparation of the first-stage aqueous liquid, 0.010g (0.057mmol) of ethylene glycol diglycidyl ether was added as an internal crosslinking agent, the rotation speed of the stirrer when obtaining the first-stage polymerization slurry liquid was changed to 425rpm, in the preparation of the second-stage aqueous liquid, 0.0116g (0.067mmol) of ethylene glycol diglycidyl ether was added as an internal crosslinking agent, in obtaining the hydrogel polymer, after cooling the inside of the separable flask system to 31°C, the total amount of the second-stage aqueous liquid was added to the first-stage polymerization slurry liquid, the amount of water extracted by azeotropic distillation of n-heptane and water was set to 275.8g, and 0.2% by mass of amorphous silica was mixed with the polymer particles in the same manner as in Example 1 to obtain 232.0g of water-absorbent resin particles. The median particle diameter of the water-absorbent resin particles was 148μm.

[0103] Comparative Example 1 The agitator blade used had two stages of four inclined paddle blades with a blade diameter of 5 cm. In the preparation of the first-stage aqueous liquid, 0.092 g (0.339 mmol) of 2,2'-azobis(2-amidinopropane) dihydrochloride and 0.018 g (0.068 mmol) of potassium persulfate were added as water-soluble radical polymerization initiators, and 0.0046 g (0.026 mmol) of ethylene glycol diglycidyl ether was added as an internal cross-linking agent. The rotation speed of the agitator when obtaining the first-stage polymerization slurry was changed to 550 rpm. In the preparation of the second-stage aqueous liquid, 2,2' 0.129g (0.475mmol) of -azobis(2-amidinopropane) dihydrochloride and 0.026g (0.095mmol) of potassium persulfate were added, 0.0116g (0.067mmol) of ethylene glycol diglycidyl ether was added as an internal crosslinking agent, the rotation speed of the stirrer when obtaining the hydrogel polymer was changed to 1000rpm, the amount of water extracted by azeotropic distillation of n-heptane and water was changed to 207.9g, and 0.2% by mass of amorphous silica relative to the mass of the polymer particles was mixed with the polymer particles, and the same procedure as in Example 1 was used to obtain 232.5g of water-absorbent resin particles. The median particle diameter of the water-absorbent resin particles was 360μm.

[0104] Comparative Example 2 The agitator blade used had two stages of four inclined paddle blades with a blade diameter of 5 cm. In the preparation of the first-stage aqueous liquid, 0.092 g (0.339 mmol) of 2,2'-azobis(2-amidinopropane) dihydrochloride and 0.018 g (0.068 mmol) of potassium persulfate were added as water-soluble radical polymerization initiators, and 0.0046 g (0.026 mmol) of ethylene glycol diglycidyl ether was added as an internal cross-linking agent. The rotation speed of the agitator when obtaining the first-stage polymerization slurry was changed to 550 rpm. In the preparation of the second-stage aqueous liquid, 2,2' 0.129g (0.475mmol) of -azobis(2-amidinopropane) dihydrochloride and 0.026g (0.095mmol) of potassium persulfate were added, 0.0116g (0.067mmol) of ethylene glycol diglycidyl ether was added as an internal crosslinking agent, the rotation speed of the stirrer when obtaining the hydrogel polymer was changed to 1000rpm, the amount of water extracted by azeotropic distillation of n-heptane and water was changed to 207.9g, and 0.2% by mass of amorphous silica was mixed with the polymer particles in the same manner as in Example 1, to obtain 229.1g of water-absorbent resin particles. The median particle diameter of the water-absorbent resin particles was 355μm.

[0105] 2. Evaluation <Saline retention capacity> The water-retention capacity of physiological saline of the water-absorbent resin particles (room temperature, 25°C ± 2°C) was measured by the following procedure. First, a cotton bag (membrane broad 60, 100mm wide x 200mm long) containing 2.0g of water-absorbent resin particles was placed in a 500mL beaker. 500g of 0.9% by mass sodium chloride aqueous solution (physiological saline) was poured into the cotton bag containing the water-absorbent resin particles at once so as not to cause any lumps, the top of the cotton bag was tied with a rubber band, and the bag was left to stand for 30 minutes to swell the water-absorbent resin particles. After 30 minutes, the cotton bag was dehydrated for 1 minute using a dehydrator (manufactured by Kokusan Co., Ltd., product number: H-122) set to a centrifugal force of 167G, and the mass Wa (g) of the cotton bag containing the swollen gel after dehydration was measured. The same operation was performed without adding the water-absorbent resin particles, the empty mass Wb (g) of the cotton bag when wet was measured, and the physiological saline water retention capacity was calculated from the following formula. Saline water retention (g / g) = [Wa-Wb] / 2.0

[0106] <Median particle size> 50 g of water-absorbent resin particles were used for measuring the median particle size. The measurement was performed in an environment with a temperature of 25±2°C and a humidity of 50±10%.

[0107] The JIS standard sieves were arranged in the following order from top to bottom: a sieve with an opening of 850 μm, a sieve with an opening of 500 μm, a sieve with an opening of 425 μm, a sieve with an opening of 300 μm, a sieve with an opening of 250 μm, a sieve with an opening of 180 μm, a sieve with an opening of 150 μm, and a tray.

[0108] The water-absorbent resin particles were placed on the top sieve of the combination, and classified in accordance with JIS Z 8815 (1994) using a Rotap type shaker (manufactured by Iida Manufacturing Co., Ltd.). After classification, the mass of the water-absorbent resin particles remaining on each sieve was calculated as a mass percentage relative to the total amount to obtain a particle size distribution. By accumulating the particles on the sieves in order from the largest particle diameter with respect to this particle size distribution, the relationship between the sieve opening and the accumulated value of the mass percentage of the water-absorbent resin particles remaining on the sieves was plotted on a logarithmic probability paper. By connecting the plots on the probability paper with a straight line, the particle size corresponding to an accumulated mass percentage of 50 mass% was determined as the median particle size.

[0109] <Measurement of Deterioration Rate> The following degradation treatment was carried out in an environment with a temperature of 25°C and a humidity of 50±10%. 15 g of water-absorbent resin particles were put into a stainless steel mixing container with an opening, a capacity of 1 L, a mouth inner diameter of 4.1 cm, a body inner diameter of 10.0 cm, and a height of 20.6 cm. A stainless steel lid was placed on the opening of the mixing container to prevent the water-absorbent resin particles from spilling out. The mixing container containing the water-absorbent resin particles was set in a cross rotary mixer (Meiwa Kogyo Co., Ltd., CM-3 type), and the mixing container in which the water-absorbent resin particles were placed was rotated for 2 hours under conditions of a rotation speed of 45 rpm and a revolution speed of 45 rpm, thereby carrying out a degradation treatment on the water-absorbent resin particles. Note that a fluctuation of ±2 rpm was allowed for the rotation speed and the revolution speed.

[0110] FIG. 4 is a schematic diagram showing the direction of rotation and the direction of revolution of the mixing vessel. Direction a in FIG. 4 (clockwise direction when viewed from above the mixing vessel 300) indicates the direction of rotation, and direction b in FIG. 4 indicates the direction of revolution. As shown in FIG. 4, the mixing vessel 300 rotates (spins) around a rotation axis C1 and also rotates (revolves) around a revolution axis C2. The rotation axis C1 is the central axis of the mixing vessel 300 in the height direction. The revolution axis C2 is located in the center of the mixing vessel 300 in the height direction and is an axis perpendicular to the rotation axis.

[0111] The deterioration rate at 3-minute value of non-pressurized DW is a value calculated by the following formula, where the 3-minute value of non-pressurized DW of the water absorbent resin particles (original material) before deterioration treatment is I, and the 3-minute value of non-pressurized DW of the water absorbent resin particles after deterioration treatment is II. [(I-II) / I] x 100

[0112] The deterioration rate at 10 minutes value of non-pressurized DW is a value calculated by the following formula, where the 10 minutes value of non-pressurized DW of the water absorbent resin particles (original material) before the deterioration treatment is III, and the 10 minutes value of non-pressurized DW of the water absorbent resin particles after the deterioration treatment is IV. [(III-IV) / III]×100

[0113] The unpressurized DW of the water-absorbent resin particles before and after the deterioration treatment was measured using a measuring device shown in Fig. 3. The measurement was carried out three times for one type of water-absorbent resin particle, and the average value of the measured values ​​was calculated. The measurement device includes a burette unit 1, a conduit 5, a measurement table 13, a nylon mesh sheet 15, a stand 11, and a clamp 3. The burette unit 1 includes a burette tube 21 with a scale, a rubber plug 23 that seals the opening at the top of the burette tube 21, a cock 22 connected to the tip of the bottom of the burette tube 21, and an air introduction tube 25 and a cock 24 connected to the bottom of the burette tube 21. The burette unit 1 is fixed with a clamp 3. The flat measurement table 13 has a through hole 13a with a diameter of 2 mm formed in its center, and is supported by a stand 11 whose height is variable. The through hole 13a of the measurement table 13 and the cock 22 of the burette unit 1 are connected by a conduit 5. The inner diameter of the conduit 5 is 6 mm.

[0114] The measurement was performed in an environment with a temperature of 25°C and a humidity of 50±10%. First, the cocks 22 and 24 of the burette part 1 were closed, and 0.9% by mass saline solution 50 adjusted to 25°C was poured into the burette tube 21 through the opening at the top of the burette tube 21. The concentration of saline solution, 0.9% by mass, is based on the mass of the saline solution. After sealing the opening of the burette tube 21 with a rubber plug 23, the cocks 22 and 24 were opened. The inside of the conduit 5 was filled with 0.9% by mass saline solution 50 so that no air bubbles were introduced. The height of the measurement table 13 was adjusted so that the height of the water surface of the 0.9% by mass saline solution 50 that had reached the through hole 13a was the same as the height of the upper surface of the measurement table 13. After the adjustment, the height of the water surface of the 0.9% by mass saline solution 50 in the burette tube 21 was read on the scale of the burette tube 21, and that position was set as the zero point (the reading at 0 seconds).

[0115] A nylon mesh sheet 15 (100 mm x 100 mm, 250 mesh, thickness about 50 μm) was laid near the through hole 13a on the measurement table 13, and a cylinder with an inner diameter of 30 mm and a height of 20 mm was placed in the center of the sheet. 1.00 g of water-absorbent resin particles 10a was uniformly spread on the cylinder. After that, the cylinder was carefully removed, and a sample in which the water-absorbent resin particles 10a were circularly dispersed in the center of the nylon mesh sheet 15 was obtained. Next, the nylon mesh sheet 15 on which the water-absorbent resin particles 10a were placed was moved quickly so that the center of the sheet was at the position of the through hole 13a, without dissipating the water-absorbent resin particles 10a, and the measurement was started. The time when air bubbles were first introduced into the burette tube 21 from the air introduction tube 25 was defined as the start of water absorption (0 seconds).

[0116] The amount of reduction in the 0.9% by mass saline solution 50 in the burette tube 21 (i.e., the amount of 0.9% by mass saline solution absorbed by the water-absorbent resin particles 10a) was successively read in increments of 0.1 mL, and the amount of reduction in the amount of 0.9% by mass saline solution 50 Wc (g) was read 3 minutes and 10 minutes after the start of water absorption by the water-absorbent resin particles 10a. From Wc, the 3-minute and 10-minute values ​​of the unpressurized DW were calculated by the following formula. The unpressurized DW is the amount of water absorbed per 1.00 g of the water-absorbent resin particles 10a. No pressure DW value (mL / g) = Wc / 1.00

[0117] <Evaluation of absorbent articles> (Evaluation of liquid leakage during use) An artificial urine having the following composition was prepared. artificial urine composition 5919.6g deionized water 60.0g NaCl 1.8g CaCl2 H2O 3.6g MgCl2 6H2O ·Food blue No. 1 (for coloring) 1% Triton X-100 15.0g

[0118] The following equipment was prepared: -Kato Tech dolls -INTEGRA liquid delivery pump (DOSEIT P910, inlet diameter 0.5cmφ) Tube (inner diameter 0.5cm) ·Electronic balance ·bat Graduated cylinder ·Thermostatic bath A graduated cylinder was used during calibration.

[0119] An INTEGRA liquid delivery pump was assembled. The test condition method was set to a test liquid input volume of 40 mL and an input speed of 8 mL / sec. The artificial urine was delivered to the tip of the tube. The tip of the tube was placed in a measuring cylinder, the liquid delivery pump was started, and the artificial urine was delivered to the measuring cylinder. The value of the measuring cylinder containing the artificial urine was read, and it was confirmed to be the set value (40 mL), and the calibration was completed.

[0120] (Production of absorbent articles) Using an airflow type mixer (Autech Co., Ltd., Pad Former), 10 g of water-absorbent resin particles and 8 g of crushed pulp were uniformly mixed by air papermaking to produce a sheet-like absorbent body of 40 cm x 12 cm in size. Next, a sheet-like absorbent body of 16 g / m2 with the same size as the sheet-like absorbent body was prepared. 2 The absorbent body was sandwiched between the two tissue papers from above and below, and pressed with a load of 196 kPa applied to the entire body for 30 seconds to obtain a laminate.

[0121] From a diaper manufactured by Procter & Gamble Japan Co., Ltd. (product name: Pampers Smooth Care, tape type, L size, purchased in 2018), the original top sheet and absorbent core were removed, and a back sheet having a pair of side gathers attached to each of the two short ends was taken. The side gathers were turned up in the short direction so that the center of the back sheet was exposed. Next, a polyethylene sheet (12 cm x 42 cm) was attached with tape glue to the central area of ​​the back sheet, excluding both longitudinal ends (width: 3 cm), to reinforce the area so as not to cover the waist gathers. Next, the absorbent body prepared as described above was placed in the center of the polyethylene sheet. Next, tape glue was placed on the back sheet along the outer periphery of the absorbent body, and then a polyethylene sheet with a basis weight of 22 g / m2 was applied. 2 A polyethylene-polypropylene air-through type porous liquid-permeable sheet (15.5 cm x 47 cm) was attached to the back sheet from above the absorbent body. The central part of the back sheet in the pair of side gathers (the part that had been turned up) was returned to its original position while being attached to the liquid-permeable sheet with tape adhesive, and an absorbent article (diaper) was obtained in which the part overlapped the liquid-permeable sheet.

[0122] (Measurement of liquid absorption amount of absorbent article) A doll (female mannequin, standing, child's anatomical model from lower abdomen to thighs, transparent) manufactured by Kato Tech Co., Ltd. was prepared in an environment of temperature 25±2°C and humidity 50±10%. The dimensions of the doll are as follows. The above test liquid was adjusted to a temperature of 25±2°C in a thermostatic chamber. After connecting the tube connected to the doll's urination part and the tube of the liquid supply pump, the test liquid was supplied to the liquid outlet of the doll's urination part. Belly circumference (around the navel): 475mm Hip circumference: 465mm Length around the base of the leg: 280mm Crotch length (length between the base of the legs): 36mm Length between navel and urination area: 145mm

[0123] After measuring the mass W1 of the absorbent article, the doll was fitted with the absorbent article. The fastening tape was attached to the doll at the tape fastening position "1" printed on the surface of the back sheet. It was confirmed that the gathers of the absorbent article were in contact with the crotch of the doll, that the gathers were standing up, that there was no bias in the length of the fitting part between the front and back of the absorbent article, and that there was no looseness around the back and stomach.

[0124] The doll was placed in the tray on its back. 40 mL of test liquid was pumped at a rate of 8 mL / sec every 5 minutes, and the pumping was repeated until leakage from the absorbent article (liquid flowing out from the back or crotch) occurred. After leakage occurred, the absorbent article was removed from the doll, and the mass W2 of the absorbent article was measured. The amount of test liquid absorbed (W2-W1) was then calculated. The results are shown in Table 1. A large amount of liquid absorption indicates that a large amount of liquid can be absorbed before leakage occurs.

[0125] [Table 1]

[0126] The degradation rate of the non-pressurized DW for 3 minutes in the embodiment before and after the degradation treatment was sufficiently smaller than that of the comparative example. The degradation rate of the non-pressurized DW for 10 minutes before and after the degradation treatment was about the same. From this, it is presumed that the degradation rate of the non-pressurized DW for 3 minutes is an effective indicator for suppressing liquid leakage during use. [Explanation of symbols]

[0127] 1...burette portion, 3...clamp, 5...conduit, 10...absorbent body, 10a...water-absorbent resin particles, 10b...fiber layer, 11...stand, 13...measuring table, 13a...through hole, 15...nylon mesh sheet, 20a, 20b...core wrap, 21...burette tube, 22...cock, 23...rubber stopper, 24...cock, 25...air introduction tube, 50...0.9% by mass saline solution, 30...liquid-permeable sheet, 40...liquid-impermeable sheet, 100...absorbent article, 200...agitating blade, 200a...shaft, 200b...flat plate portion, 300...mixing container, S...slit.

Claims

1. The deterioration rate of the non-pressurized DW at 3 minutes measured by the following procedure is 10% or less, The water retention capacity of physiological saline is 40 to 55 g / g. Water-absorbent resin particles, (1) 15 g of water-absorbent resin particles are placed in a 1 L stainless steel mixing vessel. (2) The mixing vessel in which the water-absorbent resin particles are placed is rotated for 2 hours under conditions of a rotation speed of 45 rpm and a revolution speed of 45 rpm, thereby subjecting the water-absorbent resin particles to a deterioration treatment. (3) When a three-minute value of the non-pressurized DW of the water absorbent resin particles before the deterioration treatment is I and a three-minute value of the non-pressurized DW of the water absorbent resin particles after the deterioration treatment is II, a deterioration rate at the three-minute value of the non-pressurized DW is calculated by the following formula. [(I-II) / I]×100 the water-absorbent resin particles contain a crosslinked polymer having a structural unit derived from an ethylenically unsaturated monomer, and a ratio of a total amount of (meth)acrylic acid and a salt thereof to a total amount of monomers providing structural units of the crosslinked polymer is 70 to 100 mol %, The 3-minute value of the no-pressure DW of the water absorbent resin particles before the deterioration treatment is 5 mL / g or more and 40 mL / g or less, The median particle size is 100 μm or more and 380 μm or less. Water-absorbing resin particles.

2. The water-absorbent resin particles according to claim 1, which have a water retention capacity of physiological saline of more than 40 g / g and not more than 55 g / g.

3. An absorbent comprising the water-absorbent resin particles according to claim 1 or 2.

4. An absorbent article comprising the absorbent body according to claim 3.

5. 5. The absorbent article of claim 4 which is a diaper.

Citation Information

Patent Citations

  • Production of highly water absorbing resin

    JP1994345819A

  • Absorbent member for bodily fluids having good wet integrity and relatively high concentration of absorbent polymer forming a hydrogel

    JP1997510889A

  • Production of water absorptive resin powder, water absorptive resin powder and its use

    JP2000302876A

  • Continuous coagulation device and multi-stage polymerization device provided with this

    JP2003026706A

  • Method for producing modified water-absorbing resin

    JP2007321007A